Fractal dimension: analyzing its potential as a neuroimaging biomarker for brain tumor diagnosis using machine learning - Battalapalli, Dheerendranath; Vidyadharan, Sreejith; Prabhakar Rao, B. V. V. S. N.; Yogeeswari, P.; Kesavadas, C.; Rajagopalan, Venkateswaran (Frontiers in Physiology, 2023)
▪ A comprehensive set of fractal dimension (FD) features werefractal dimension (FD) feature set was extracted from tumorous and non-tumorous brain regions.▪ Texture features were also measured in the tumorous and non-tumorous brain regions.▪ FD features showed superior performance in classifying low-grade glioma (LGG) from high-grade glioma (HGG).▪ Interestingly non-tumorous FD features also distinguished LGG from HGG, suggesting that the pathophysiological process of the tumor may not be local.